Direct comparison of (99m)Tc-PSMA SPECT/CT and (68)Ga-PSMA PET/CT in patients with prostate cancer - Albalooshi, Batool (Asia Ocean J Nucl Med Biol, 2020)
OBJECTIVE(S): (99m)Tc-PSMA SPECT/CT is a cost effective alternative for (68)Ga-PSMA PET/CT. The aim of this study was to directly compare these two techniques in patients with prostate cancer. METHODS: 28 man with prostate cancer were studied using (99m)Tc-PSMA SPECT/CT and (68)Ga-PSMA PET/CT in a short time period (<60 days). No intervention was done between the studies. Whole body PET/CT was done 60 minutes after IV injection of 2 MBq/Kg of (68)Ga-PSMA. (99m)Tc-PSMA kit (PSMA I+S) was used for SPECT/CT and whole body imaging was performed 4 hours after IV injection of 740 MBq of (99m)Tc-PSMA. Images were interpreted independently and the results of each imaging were recorded. RESULTS: The mean age of the patients was 64.7±9.6 years old and the mean time difference between two sets of images was 16.6±13.5 days. Abnormal uptake was seen in 25 (89.2%) patients by (68)Ga-PSMA PET/CT and 20 (71.4%) patients with (99m)Tc-PSMA SPECT/CT. No patients with positive (99m)Tc-PSMA SPECT/CT had negative (68)Ga-PSMA PET/CT. The mean number of detected lesions was 26.07±27.5 by (68)Ga-PSMA PET/CT and 10.52±10.99 by (99m)Tc-PSMA SPECT/CT (P<0.001). Detection of lymph nodes and bone metastases were not significantly different between two sets of imaging (P>0.05), however (68)Ga-PSMA PET/CT were more successful in detection of prostate bed lesions compared to (99m)Tc-PSMA scan. Interestingly, no patient with PSA level of >2.1 ng/ml had discordant result between two sets of images. CONCLUSION: (99m)Tc-PSMA SPECT/CT is as accurate as (68)Ga-PSMA PET/CT in M staging, however (68)Ga-PSMA PET/CT detected more lesions compared to (99m)Tc-PSMA SPECT/CT. Detection rate was not significantly different between two techniques in patients with PSA levels>2.1 ng/ml.